Access to veterinary care in Canada: a cross-sectional survey of animal healthcare organizations and interventions - Rausch, Quinn; Alhamdan, Maryam; Bateman, Shane; Evason, Michelle; Fraser-Celin, Valli; Graham, Courtney; Saad, Jamie; Tuma, Michelle; Ward, Karen; Van Patter, Lauren (Frontiers in Veterinary Science, 2025)
IntroductionMany Canadians struggle to access healthcare for their animals, but little data is available from the Canadian context on how barriers to care are being addressed, and with what effects.MethodsThe aim of this research was to characterize service providing organizations, barrier mitigation tools, community partnerships, and evaluation metrics used by organizations attempting to increase access to animal healthcare in Canada. In this study, we conducted online data mining and a cross-sectional, mixed-methods organizational survey.ResultsResponses to the survey (N = 97) were received from non-profit organizations (52%), for-profit clinics (38%), and several municipal or governmental services (4%) and educational institutes (5%). Commonly reported tools included no cost or low-cost services, pop-up clinics and providing items to assist with pet transportation, with many other tools (payment plans without a credit check, services in multiple languages, availability of assistive technology) being employed by fewer than 20% of responding organizations. Only 38% of organizations used at least one tool from each of the four categories of barriers. Community involvement in programs ranged from simply accessing the service when it was available (outreach) to giving occasional feedback on their experiences (consulting), being employed or volunteering in program provision (collaborating), and community leadership partnering on initiatives (sharing leadership). Program evaluation most often involved quantitative measures of service usage with fewer organizations formally soliciting feedback from the community or looking at long-term health impacts.DiscussionResponses demonstrate that organizations employ a wide range of tools to mitigate access to veterinary care barriers primarily along financial and geographical lines, and to a lesser extent with tools targeting cultural or disability-related barriers highlighting the importance of building capacity around addressing multiple intersecting barriers. Study findings provide a baseline characterization of current efforts by Canadian organizations to mitigate barriers to accessing animal healthcare.